Relationship between Nutritional Status of Adolescent Girls and the Incidence of Adolescent Girls' Anemia in Seven Villages - Louisa Ariantje Langi; Ida Bagus Eka Utama Wija (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anemia in adolescent girls is a significant public health problem, especially in rural areas. One of the main risk factors for anemia is poor nutritional status. Adolescent girls with unbalanced nutritional status have a higher risk of iron deficiency, leading to anemia. This study aims to determine the relationship between nutritional status and the incidence of anemia in adolescent girls in seven villages in the Rancakalong Health Center working area in 2023. Aims: to determine whether there is a relationship between nutritional status and the incidence of anemia in adolescent girls in seven villages in Rancakalong sub-district. Methods: This study used an observational analytical design with a cross-sectional approach. The subjects were adolescent girls aged 13–18 years who lived in seven villages in the Rancakalong Health Center working area. Nutritional status was measured based on Body Mass Index (BMI) according to age, while the Sahli method determined anemia based on hemoglobin levels. Data analysis was carried out using the chi-square test to see the relationship between nutritional status and the incidence of anemia. Results: Of the 140 adolescent girls studied, 23 (16.4%) had anemia. One person (4.3%) with anemia had poor nutritional status. The results of the analysis showed no significant relationship between nutritional status and the incidence of anemia (p > 0.05) with the results of the chi-square p-value analysis of 0.443. Conclusion: There is a significant relationship between nutritional status and the incidence of anemia in adolescent girls in the Rancakalong Health Center working area. Sustainable nutritional intervention and health promotion are needed to improve nutritional status and reduce the incidence of anemia in adolescent girls.